Collection and integration of scientific data for production analysis Brazilian scientific in open access journals - Magela Dias, Thiago; Mascarenhas Dias, Patricia; Farias Moita, Gray (Advanced Notes in Information Science, 2022)
This work aims to analyze publications in journals by Brazilian researchers in order to verify the adoption of open access journals for dissemination of their research results in different areas of knowledge. To perform the analysis, those PhD graduated with CVs registered in the Lattes Platform were considered. We evidenced that, in recent years, the publication of works on this topic has increased substantially. Some areas of knowledge have greater adherence to this means of communication, to the detriment of others, which tend to disseminate their research in other media, such as books and articles in conference proceedings. Consequently, several other studies can be carried out, such as verifying the impact of these publications, either by the number of citations per article, or by means of other metrics.